Lessons from my school - Miller, Paul; Voon, Derby (Blackwell Publishing Asia, 2011)
This article presents analyses of the NationalAssessment Program – Literacy and Numeracy(NAPLAN) data and data on other indicatorsthat are made available through theMy School website. There are large differencesacross states and types of schools (independent,Catholic and government) in the Year3 NAPLAN outcomes, though the differencesacross states tend to diminish as outcomes forlater years of study are examined. Some schoolsare shown to consistently have academic outcomesbetter than their characteristics wouldotherwise indicate; conversely, other schoolsare shown to consistently have academic outcomesbelow the levels their characteristicswould otherwise indicate. Few of these differencesare statistically significant.